2021
DOI: 10.1155/2021/2632343
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Coated Balloon-Only Angioplasty Outcomes in Diabetic and Nondiabetic Patients with De Novo Small Coronary Vessels Disease

Abstract: Background. The revascularization of small vessels using drug-eluting stents remains challenging. The use of the drug-coated balloon is an attractive therapeutic strategy in de novo lesions in small coronary vessels, particularly in the diabetic group. This study aimed to assess the outcomes of DCB-only angioplasty in small vessel disease. Methods. A total of 1198 patients with small vessel disease treated with DCB-only strategy were followed. Patients were divided into the diabetic and nondiabetic groups. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Recently, two prospective studies specifically evaluated the safety and efficacy of DCB in this setting 58,59 . As expected, both studies reported that the diabetic group treated with DCB was associated with a higher incidence of 1-year TLF (5.36% vs 2.77%; OR 1.991, 95% CI: 1.077-3.681; 3.9% vs 1.4%; HR 2.712, 95% CI: 1.254-5.864) and TLR (4.15% vs 1.90%; OR 2.233, 95% CI: 1.083-4.602; 2.0% vs 0.5%; HR 3.698, CI: 1.112-12.298) as compared to non-diabetic patients, whereas the rates of MI (OR 4.042, 95% CI: 0.855-19.117; p=0.057; 0.6% vs 0.1%; p=0.110) were not significantly different.…”
Section: The Role Of Dcb In Patients With Diabetes Mellitusmentioning
confidence: 99%
“…Recently, two prospective studies specifically evaluated the safety and efficacy of DCB in this setting 58,59 . As expected, both studies reported that the diabetic group treated with DCB was associated with a higher incidence of 1-year TLF (5.36% vs 2.77%; OR 1.991, 95% CI: 1.077-3.681; 3.9% vs 1.4%; HR 2.712, 95% CI: 1.254-5.864) and TLR (4.15% vs 1.90%; OR 2.233, 95% CI: 1.083-4.602; 2.0% vs 0.5%; HR 3.698, CI: 1.112-12.298) as compared to non-diabetic patients, whereas the rates of MI (OR 4.042, 95% CI: 0.855-19.117; p=0.057; 0.6% vs 0.1%; p=0.110) were not significantly different.…”
Section: The Role Of Dcb In Patients With Diabetes Mellitusmentioning
confidence: 99%
“…Every year, 30-50% of all-comers coronary intervention methods are accomplished on human beings with small artery coronary disease, that`s a mentioned predictor of awful consequences following PCI [1][2][3][4]. Determining the most effective approach for treating coronary disease in tiny vessels is incredibly difficult [5].…”
Section: Introductionmentioning
confidence: 99%